The Relation between Christianity and Colonialism in Ngugi Wa Thiongos The River Between - Tatang Iskarna (Universitas Sanata Dharma, 2018)
This article is aimed at describing how the relation between Christianity and colonialism is constructed in The River Between (1965), a novel by Ngugi wa Thiongo. Using postcolonial approach focusing on the analysis of the characters and conflicts, this study reveals the mutual relation between Christianity and colonialism. Christianity becomes the ideological apparatus to build a colonial myth, doctrine, or perspective, while Christian missionaries gain the colonizers support from the colonial administrators. Their antagonistic relation can be explored through the natives re-reading of the Bible to review the colonialism and get rid of the colonial bondage. As postcolonial literature, The River Between offers counter-discourse against colonialism. However, some parts of the text are still slipped in the colonial hegemony.Keywords: Christianity, colonialism, postcolonialism, ideological apparatus, counter-discourse